Profil Reproduksi Jantan Tikus (Rattus norvegicus Berkenhout, 1769) Galur Wistar Stadia Muda, Pradewasa, dan Dewasa - Laksmindra Fitria; Mulyati Muyati; Cut M. Tiraya; Andreas S. Budi (Jurnal Biologi Papua, 2015)
Reproductive biology is one of prominent studies in biomedical research. Disruption in reproductive system becomes a major problem both in humans and animals. Preclinical study using animal model is therefore needed to initiate clinical studies and diagnostic purposes. Wistar rats are commonly used for research in male and female reproductive system due to their representation of mammal biological system. For that purpose, their reproductive age must be determined to meet the aim of studies. This research was carried out to provide reproductive profile of normal male Wistar rats from different ages, furthermore categorizing them into three checkpoints: young, subadult, and adult. Variables observed including: body mass, testosterone level, reproductive glands index, spermatogenesis, and sperm analysis. Results demonstrated that body mass, testosterone level, and reproductive glands index increase with age (significant at the age of 6–7 weeks). Spermatogenesis is initiated at the age of 7 weeks, characterized by significant increase in the number of spermatogenic cells which then maintained at subsequent ages. Spermatozoa has been produced at the age of 6 weeks, however still in low concentration, immotile, and not viable. The quantity and quality of sperm also increase with age. At the age of 8–9 weeks, sperm concentration significantly increases, progressive movement occurs, and viability is close to 100 %. In conclusion, rats aged 4–5 weeks can be categorized as young, sexually immature; rats aged 6–7 weeks are subadult, the reproductive system has well-developed (puberty) but spermatozoa are still immotile (infertile); rats aged 8–9 weeks are adult, sexually mature, and ready for mating, thus suitable as animal model for the study of reproductive system.Key words: Wistar rats, reproductive system, testosterone, spermatogenesis, spermatozoa.